Aspirations on Hold : Young Lives in the West Bank and Gaza - World Bank (Washington, DC, 2017)
Seventy percent of West Bank and Gaza's population is under the age of 30, and their share will continue to grow in the years ahead. The aspirations and ambitions of this large and growing population of children and youth have the potential to define the future of the West Bank and Gaza. This assessment seeks to contribute to the understanding of factors driving the choices of young men and women at this critical juncture of their lives, with a particular emphasis on the roles that changing gender norms and the conflict environment are having on their aspirations for education, jobs, and forming families. Young Palestinians are moving into adulthood in a world surrounded by roadblocks and barriers, and gripped by soaring unemployment and uncertainty about what their futures may hold. Still, this generation remains optimistic and ambitious. They are pursuing high school and college degrees, and hanging on to expectations for better jobs and better lives than was possible for their parent's generation. In the face of such bleak prospects, why? What is driving these youth's aspirations for high levels of education and good jobs? To provide a broad context for the youth's testimonies, this report first takes stock of developments affecting the West Bank and Gaza over the past decade. In this period, the Palestinian territories witnessed two major episodes of conflict: the second intifada beginning in 2000 and the crisis in Gaza in 2007. Both episodes had severe and wide-ranging economic repercussions, and were accompanied by restrictions on internal and external mobility of people and goods. As a result, in the last decade, the West Bank and Gaza has witnessed economic volatility without parallel (even in comparison to countries affected by large financial crises), massive spikes in poverty, and some of the highest rates of unemployment in the world. Young people's unemployment rates are even higher, and much more so for young women. The youth's focus groups indicate that traditional gender norms remain very strong in their society, and mainly seem to be reinforced by the difficult conflict environment. Men's status as the breadwinners means that boys, especially from poor families, are likely to withdraw from school sooner than girls in order to take up income earning roles; and the weak economy intensifies these pressures.